Murder Ballads and Legends - Hrabal, Bohumil, 1914-1997 (Book collections on Project MUSE., 2018)
"This translation is based on the first edition of Morytáty a legendy, published in 1968 by Československý spisovatel. The images that accompany each story are from woodcuts originally created for old broadside ballads and reproduced as illustrations for that first edition. Morytáty a legendy arrived in the early months of the Prague Spring ... Morytáty a legendy was a collection of unpublished short stories, some new and some old. The author's "post scripts" contain his comments at the time of publication and represent a self-effacing running commentary on his method, which mines pub tales and urban folklore for material. The post scripts offer everything from needed explanatory notes ("A Legend Played on Strings Stretched between Cradle and Coffin") to outright mystification ("The Ballad of the Queen of the Night") to an epilogue four times the length of the story itself ("The Legend of Egon Bondy and Vladimírek"). The "Vladimírek" epilogue provides a foretaste of The Tender Barbarian (Něžný barbar, completed 1973), Hrabal's autobiographical tribute to the artist Vladimír Boudník, who would die suddenly at the end of 1968. At the book's heart is "The Legend of Cain," a bleak story written nearly twenty years earlier and the basis for the novella Closely Watched Trains (Ostře sledovane vlaky, 1965)"--